Selection of materials and manufacturing processes for green engineering - Haque, Md. Mohafizul; Ismail, Ahmad Faris; Alias, Tuti Yasmin (2009)
Pollution free environment is now-a-day considered as an important criterion of development for almost every country of the world. Thus, selection of materials and manufacturing processes for a particular product becomes very crucial and must pass through numerous regulations to achieve green atmosphere. In order to achieve this goal, close coordination among the designer, material scientist, manufacturing engineer and environmental expert is needed. Starting from the design to the final product including the recyclability and waste disposal, each and every step must be carefully considered, planned and coordinated before manufacturing starts. This is because; any change in design or material and associated technique during manufacturing becomes more and more expensive as work progresses. Agro-based and industrial nations of the world have started to show their interest on health hazard, recyclability and to generate clean and environment friendly energy. At the same time, emphasis must be given on pollution free green environment so that man-made disaster may not occur.